An Early Bronze Age Incense Burner from Dahwa (DH1), Northern al-Batinah, Oman - Ğawharī, Nāṣir Saʻīd ʻAlī al- (Near Eastern archaeology, 2021)
The Early Bronze Age in the Oman Peninsula is marked by two local cultures: Hafit (ca. 3400-2500 BCE), which is notable for thousands of burials (cairns and beehives) spread over large areas in northern Oman and the lack of settlement remains; and Umm an-Nar (2500-2000 BCE) marked by the first permanent settlements, intensive exploitation of copper, and international trade, mainly with Mesopotamia and the Indus Valley (Potts 1990a: 102-6; 1993: 423-27; Cleuziou 2003; Al-Jahwari 2009, 2013). Five Early Bronze Age sites (DH1, DH5, DH6, DH7, and DH8) have been found in the Dahwa region clustered within an area not longer than 1.7 km. They are distributed on both sides of Wadi al-Sukhun and in the bottom of the wadi itself (Al-Jahwari et al. 2018: 29-30).The location of the sites in the Dahwa region were chosen carefully for several reasons. Primary among these were the water sources: the Dahwa region is located where two major wadis converge. Copper resources were another factor. Also important was the presence of a trade route: Dahwa is a key region connecting the coastal plain to the inland region, such as Hili, Yanqul, and Dhank.